FITOREMEDIASI LOGAM MERKURI (Hg) PADA MEDIA AIR OLEH KANGKUNG AIR (Ipomoea aquatica Forsk.) - Sinulingga, Nuriah (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2015)
This study aims to determine the ability of watercress plants in absorbing mercury (Hg). Mercury is one type of heavy metals dangerous and toxic (Hakim, 2003). If the amount in the water has crossed the threshold will cause pollution. For that required effort to minimize the levels of Hg metal before the waste into the waters, such as by using watercress plants as phytoremediation agent. Research was conducted experimentally. The purpose of this study is to know the ability of watercress in accumulating mercury in water media.Phytoremediation media in the form of HgNO3 solution with concentration 0,5 and 1 ppm and addition of NPK 1 gram in insert plastic container as much as 1 liter. Measurements of Hg concentration in plants were performed on day 5, 10, 15 using SSA. The resulting data is processed using qualitative method of descriptive. The result showed that there was no accumulation of mercury in watercress concentration of 0,5 and 1 ppm during exposure 5, 10, 15 days, and concentration 5 ppm during exposure 5 and 10 days, but accumulated at concentration 5 ppm for 15 days exposure that is equal to 0,116 ppm, therefore watercress is still safe from mercury at low concentration of 0,5 and 1 ppm, but dangerous at concentration of 5 ppm.